Entrapment of Natural Flavonoids for Microparticulate Drug Delivery System for Hydrophobic Drug Rutin and Hesperidin - Bordoloi, Ripunjoy; Deb, Pulak; Gogoi, Barnali; Baishya, Himakshi; Gogoi, Parthajyoti (Asian Journal of Chemistry, 2018)
The aim of this study was to investigate importance of polymeric micro particulate drug delivery system in pharmaceutical field for modifying the drug profile of poorly water-soluble drug rutin and hesperidin. In this study sodium alginate is used as a polymer for entrapping the model drug, which involved the method of ionic cross linking- process. For physico-chemical characterization of the formulations we have studied in vitro drug release drug entrapment efficiency, Fourier transforms infrared spectroscopy (FTIR), scanning electron microscopy (SEM) and differential scanning calorimetric (DSC). In case of hesperidin FH1 is having the minimum drug entrapment efficiency of approximately 69.46 % whereas the entrapment efficiency of FH5 shows an approximate entrapment of 74.28 %. Drug:sodium alginate ratio of 1:2 shows an approximate entrapment of 74.28 %. In case of hesperidin FH2 is having the minimum drug entrapment efficiency of approximately 71.00 % whereas the entrapment efficiency of FH2 shows an approximate entrapment of 75.7 %. This could be revealed as the increase in polymer concentration has significant effect on the drug entrapment efficiency. Drug:sodium alginate ratio of 1:1.2 shows an approximate entrapment of 75.7 %. The FTIR analysis of drug, polymers and the formulations indicated the compatibility of the drug with the polymers. The scanning electron microscopy was used to confirm the smoothness of microspheres formulated. The results of the dissolution study indicated that with the increase in the concentration of sodium alginate in the matrix the amount of drug release appreciably decreased and became steady. The drug-polymer interaction in the microsphere was studied by using differential scanning calorimetry. The release kinetics of the prepared batches of formulation was also studied and was found that the prepared batches followed Higuchi and Krosmayer Peppas release mechanism. The findings of the study suggest that the microsphere formulations is a promising carrier for flavanoids delivery and can be considered as a favourable oral controlled release dosage form for hydrophobic drug rutin and hesperidin.